Islamic Burials and Funerary Rites. Toledo as a Case-Study for the Evolution from Andalusi to Mudejar - Ana ECHEVARRÍA ARSUAGA (Studia Historica. Historia Medieval, 2020)
This article will use a range of sources to show traces of continuity or breakdown among the Islamic population of Toledo from Andalusi to Mudejar times. The archaeological information from the campaigns in Toledo’s cemeteries will provide a contrast with Christian and Arabic written sources about the location of their grounds and the practical limitations accorded by Christians to burial customs. The corpus of Islamic literature includes theoretical treatises of fiq?, Islamic breviaries –one of them from Ocaña, a nearby town in the cultural zone of influence of Toledo– and the proceedings of the meetings of a sufi confraternity in Toledo (active c. 1400-1420).